2017
DOI: 10.1021/acs.macromol.7b01193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aggregation States and Physical Properties of Syndiotactic Polystyrene/Hydrogenated Polyisoprene Multiblock Copolymers with Crystalline Hard Domain

Abstract: Molecular aggregation structure and mechanical as well as thermal properties of novel well-defined multiblock copolymers consisting of crystalline syndiotactic polystyrene (sPS) and rubbery hydrogenated polyisoprene (hPIp) were investigated. The morphology and crystalline ordered structure of the multiblock copolymer films prepared by solvent casting from 1,2-dichlorobenzene solution depended on the volume fraction of sPS (VF sPS ) and number of blocks. The multiblock copolymer films exhibited ordered morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The orientation of the PEB chains during sample deformation is also crucial for understanding the mechanical properties of the material. In situ small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) techniques are powerful methods to investigate the arrangement and deformation behavior of PS domains as well as the orientation state of the PEB chains. Many studies have reported on the deformation behavior of various types of thermoplastic elastomers based on these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of the PEB chains during sample deformation is also crucial for understanding the mechanical properties of the material. In situ small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) techniques are powerful methods to investigate the arrangement and deformation behavior of PS domains as well as the orientation state of the PEB chains. Many studies have reported on the deformation behavior of various types of thermoplastic elastomers based on these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Multiblock copolymers (MBCs) containing random (ABBAAB) and alternating (ABABAB) segments have attracted significant scientific interest, owing to their resulting microphase‐separated morphologies, different thermal and mechanical properties with a growing list of realized and potential applications . Currently, major sy nthesis methods to get MBCs relying on polycondensation can be divided into two categories, that is, click chemistry and coupling chemistry of α,ω‐dihydroxy to form urethane, ester, or amide bonds .…”
Section: The Synthesis Of Mbcs Using Different Macromonomersmentioning
confidence: 99%
“…Currently, major sy nthesis methods to get MBCs relying on polycondensation can be divided into two categories, that is, click chemistry and coupling chemistry of α,ω‐dihydroxy to form urethane, ester, or amide bonds . Although some of the MBCs have been successfully prepared and got some applications, those MBCs were mainly focused on thermoplastic materials with superior performance . Therefore, having a special terminal groups of MBCs which can be used as thermosetting material were not yet received much attention and research.…”
Section: The Synthesis Of Mbcs Using Different Macromonomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Imposing deformation on TPEs may induce complex structural evolutions simultaneously, such as deformation of microphase‐separated domains, crystallization in soft domains, melting or phase transition in hard domains, and so forth . These structural evolutions can be tracked with in situ small‐ and wide‐angle X‐ray scattering (SAXS/WAXS) techniques . For example, with in situ SR WAXS during cyclic tensile deformation on polyamide 12 (PA12) and polytetrahydrofuran segmented copolymers, a reversible transformation between the stable γ phase to the metastable α″ phase of PA12 is observed, which may contribute somewhat to their elasticity .…”
Section: Introductionmentioning
confidence: 99%